KONSERVASI PAMELO Citrus maxima (Burm.) Merr. DENGAN PENURUNAN KONSENTRASI MEDIUM DAN SUKROSA - Tyas, Kartika Ning; Susanto, Slamet; Dewi, Iswari S; Khumaida, Nurul (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2012)
Indonesia has high variety of pummelo [Citrus maxima (Burm.) Merr.], but only several cultivar are cultivated extensively. Others became vurnerable and the germplasm has to be conserved to prevent their extinction. One of the conservation method is in vitro conservation using a slow growth technique. Factorial experiment was used in designing the experiment, the first factor was MS medium concentration, i.e. 1/2MS and MS. The second factor was sucrose concentration, i.e. 0; 1; 2; and 3%. The results showed that low concentration of MS medium and sucrose reducing the leaf number and shoot length but increasing the root number and length. Based on inhibition of growth, the most reducing growth was planlet on MS without sucrose.